Tailoring Electron Diffusion in Electrospun Metal Oxide Nanostructures for Dye-sensitized Solar Cells - Rajan, Jose; P. S., Archana; A., Le Viet; E., Naveen Kumar; M. M., Yusoff; S., Ramakrishna (2011)
Metal oxide wide bandgap semiconducting nanostructures lie at the heart of many technologies including dye-sensitized solar cells (DSCs), they act as charge separation and transport medium; and therefore, understanding and controlling charge transport is key to increase the performance level of corresponding devices beyond current thersholds. Unlike bulk semiconductors, in which the electrons diffuses in the conduction band from one transport state to another, electron transport in nanostructured materials occurs through the localized surface energy states that lie within the bandgap. This article focus on the advances made on controlling the charge transport in electrospun metal oxide nanostructures.